Comparison between the effects of potassium phosphite and chitosan on changes in the concentration of Cucurbitacin E and on antibacterial property of Cucumis sativus - Moazzameh Ramezani; Fatemeh Rahmani; Ali Dehestani (BMC, 2017)
Abstract Background Cucurbitacins are mostly found in the members of the family Cucurbitaceae and are responsible for the bitter taste of cucumber. Pharmacological activities such as anti-bacterial and anti-tumor effects have been attributed to these structurally divers triterpens. The aim of this study was to investigate the effect of potassium phosphite (KPhi) and chitosan on Cucurbitacin E (CuE) concentration in different tissues of Cucumis sativus. The antibacterial effect of plant ethanolic extracts was also examined against E.coli PTCC 1399 and Pseudomonas aeruginosa PTCC 1430 bacterial strains. Methods After emergence of secondary leaves, cucumber plants were divided into 4 groups (each group consisted of 6 pots and each pot contained one plant) and different treatments performed as follows: group1. Leaves were sprayed with distilled water (Control), group 2. The leaves were solely treated with potassium phosphite (KPhi), group 3. Leaves were solely sprayed with chitosan (Chitosan), group 4. Leaves were treated with KPhi and chitosan (KPhi + chitosan). The KPhi (2 g L−1) and chitosan (0.2 g L−1) were applied twice every 12 h for one day. Fruits, roots and leaves were harvested 24 h later. The ethanolic extract of plant organs was used for determination of CuE concentration using HPLC approach. The antimicrobial activity was evaluated by the agar well diffusion method. The experiments were arranged in a completely randomized design (CRD) and performed in six biological replications for each treatment. Analysis of variance was performed by one-way ANOVA and Dunnette multiple comparison using SPSS. Results The highest level of CuE was recorded in fruit (2.2 g L−1) of plants under concomitant applications of KPhi and chitosan. Result of antibacterial activity evaluation showed that under concomitant treatments of KPhi and chitosan, fruit extract exhibited the highest potential for activity against E. coli PTCC 1399 (with mean zone of inhibition equal to 36 mm) and Pseudomonas aeruginosa PTCC 1430 (with mean zone of inhibition equal to 33 mm). Conclusions KPhi and chitosan can induce production of CuE compound and increase antibacterial potential of cucumber plant extract. The application of KPhi and chitosan may be considered as promising prospect in the biotechnological production of CuE.